Career development programs and career adaptability among students: A systematic literature review - Afda Lianti; Arif Sahin (Universitas Mercu Buana Yogyakarta, 2025)
Career adaptability (CA) is conceptualized within career construction theory (CCT) as a composite of four dimensions: concern, control, curiosity, and confidence. It serves as a critical psychosocial resource. It enables individuals, particularly university students, to navigate developmental tasks, career transitions, and emerging challenges within the rapidly evolving Industry 5.0 landscape. However, the gaps within the existing studies show the unidentified of the relationship between career development programs and students’ CA. Therefore, this study was conducted using a systematic review framework employing thematic synthesis. It integrates evidence from 18 empirical studies published between 2019 and 2024 that focused on university and late-adolescent populations across diverse cultural and educational contexts. Findings revealed the structured career development programs incorporates experiential learning, reflective practice, and social support mechanisms. These consistently enhance students’ adaptability, although the magnitude of effectiveness varies according to program design, duration, and contextual fit. The futher synthesis identified three overarching clusters of influencing factors: (1) personal motivational factors such as proactive personality, grit, and career self-efficacy; (2) socio-contextual factors including parental autonomy support and age-related stereotypes; and (3) digital behavioral factors, such as short-video overuse. By systematically integrating insights from both CCT and social cognitive career theory (SCCT), this review study advances prior literature that significantly treated these frameworks in isolation or focused on general populations without contextualizing interventions for students. Conceptually, this study maps the interaction of multilevel determinants in shaping adaptive career readiness; methodologically, it provides an evidence-based synthesis of program characteristics linked to measurable adaptability outcomes. Practically, the findings underscore the necessity of designing holistic, context-sensitive, and evidence-driven career development programs that address psychological, social, and digital dimensions of adaptability. Therefore, higher education institutions (HEIs) are encouraged to embed experiential, reflective, and digital-literacy components within career centers to foster sustainable adaptability aligned with the dynamic demands of the Industry 5.0 workforce. Keywords: Ethical issues, intellectual property, plagiarism, plagiarism checking tools, research writing.